La peinture russe contemporaine. (Paris : Palais des Congrès, 1976)
Alexeiev, Alexandre ; Arkhangelsky, Maxime ; Bakhitchinian, Vagritch ; Belenok, Petr ; Bourdjelian, Mikhail ; Birger, Boris ; Brui, William ; Broussilovski, Anatoly ; Chemiakine, Dorothéa ; Chemiakine, Mikhail ; Chelkovsky, Igor ; Elinson, Harry ; Faif, Garry ; Galatski, Vladimir ; etc.
La peinture russe contemporaine, Palais des Congrès, Paris, 1976
boek
Keywords: Rusland